THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE WORK ENGAGEMENT IN CLASS IIA COMMUNITY INSTITUTIONS PURWOKERTO - Hafidh, Fatkhul; Rachmayanthy, Rachmayanthy (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This research aims to see the influence of transformational leadership on employee work engagement at the Class IIA Purwokerto Penitentiary. This research method uses quantitative methods with primary data obtained from 88 employees of the Purwokerto Class IIA Community Institution. There are a total of 32 statement items whose answers will then be processed into research results using SPSS. The results of the determination test analysis show that the influence of transformational leadership on employee work engagement is 37.4%. The hypothesis of this research concludes that there is an influence of transformational leadership on employee work engagement at the Class IIA Purwokerto Penitentiary. Keywords: Transformational Leadership; Job Engagement; Correctional Institutions